Incidence and management of inguinodynia after inguinal plasty - Granados-Romero, Juan J.; Ceballos-Villalva, Jesus C.; García-Olivo, Israel; Jonathan E., Cruz Escobar; Corona-Torres, María J.; Mondragón-Cordero, Alba M.; Lourdes A., Quintero Arías; Henry, Ayala García; Juan C., Vázquez González; Contreras-Flores, Ericka H. (International Journal of Research in Medical Sciences, 2020)
Background: Hernia is defined as a defect of fascial and muscle-aponeurotic structures, allowing the protrusion of elements. The most frequent is inguinal region, prevailing in men 3:1 vs female. The most frequent complications are persistent chronic pain. Methods: A descriptive, prospective and cross-sectional study was performed in postoperative inguinal plasty patients, using a laparoscopic approach and open approach, the presence or absence of inguinodynia was studied using the visual analogue pain scale (VAS) and the Semmes-Weinstein monofilament, in addition to a systematic investigation in the following PubMed, Medline, Clinical Key and Index Medicus databases, with articles from July 2019 to April 2020. Results: Inguinodynia was present in laparoscopic surgery and open approach, 58 patients had inguinodynia at two weeks associated with the inflammatory response of the tissues and the presence of a foreign body (mesh), 77% of the patients with persistence of pain at 3 months reported mild pain (VAS 1-4), 21% moderate pain that did not limit their daily activities (VAS 5-8) and 2% of the patients reported severe pain which limited physical activity and effort (VAS 9-10). Conclusions: Inguinodynia has an impact on hospital costs and quality life, we consider it is essential to domain the anatomical variants of the region. We propose an extensive follow-up of this group of patients, to make a comparison of diagnostic methods, as well as conservative management vs. modern techniques for pain control.